(untitled) (Proximus Journal of Sports Science and Physical Education, 2025)
The study aimed to identify the relationship between specific physical abilities and certain offensive skills of goalkeepers in the Iraqi Professional Football League. The researchers hypothesized a statistically significant relationship between these physical abilities and offensive skills among the study sample.